# Extensions 1→N→G→Q→1 with N=3- 1+2 and Q=C3×C6

Direct product G=N×Q with N=3- 1+2 and Q=C3×C6
dρLabelID
C3×C6×3- 1+2162C3xC6xES-(3,1)486,252

Semidirect products G=N:Q with N=3- 1+2 and Q=C3×C6
extensionφ:Q→Out NdρLabelID
3- 1+21(C3×C6) = C6×C3≀C3φ: C3×C6/C6C3 ⊆ Out 3- 1+254ES-(3,1):1(C3xC6)486,210
3- 1+22(C3×C6) = C6×He3.C3φ: C3×C6/C6C3 ⊆ Out 3- 1+2162ES-(3,1):2(C3xC6)486,211
3- 1+23(C3×C6) = C2×C33⋊C32φ: C3×C6/C6C3 ⊆ Out 3- 1+2549ES-(3,1):3(C3xC6)486,215
3- 1+24(C3×C6) = C2×He3.C32φ: C3×C6/C6C3 ⊆ Out 3- 1+2549ES-(3,1):4(C3xC6)486,216
3- 1+25(C3×C6) = C32×C9⋊C6φ: C3×C6/C32C2 ⊆ Out 3- 1+254ES-(3,1):5(C3xC6)486,224
3- 1+26(C3×C6) = C6×C9○He3φ: trivial image162ES-(3,1):6(C3xC6)486,253
3- 1+27(C3×C6) = C2×3- 1+4φ: trivial image549ES-(3,1):7(C3xC6)486,255

Non-split extensions G=N.Q with N=3- 1+2 and Q=C3×C6
extensionφ:Q→Out NdρLabelID
3- 1+2.1(C3×C6) = C6×C3.He3φ: C3×C6/C6C3 ⊆ Out 3- 1+2162ES-(3,1).1(C3xC6)486,213
3- 1+2.2(C3×C6) = C2×C9.He3φ: C3×C6/C6C3 ⊆ Out 3- 1+2543ES-(3,1).2(C3xC6)486,214
3- 1+2.3(C3×C6) = C2×C32.C33φ: C3×C6/C6C3 ⊆ Out 3- 1+2549ES-(3,1).3(C3xC6)486,218
3- 1+2.4(C3×C6) = C2×C9.2He3φ: C3×C6/C6C3 ⊆ Out 3- 1+2549ES-(3,1).4(C3xC6)486,219

׿
×
𝔽